An in vitro evaluation of fat-extracted pongamia seedcake in barley-based feedlot diets - Ahmed, Eslam; Ni, Mingbo; Chaves, Alex V.; Meale, Sarah J. (Frontiers in Animal Science, 2025)
There is growing interest in identifying alternative sustainable feed ingredients for ruminant diets. This study evaluated four processed pongamia seedcake (PSC) meals—three produced using a proprietary extraction method and one by traditional hexane extraction—in two separate in vitro experiments. Experiment 1 assessed PSC as a partial replacement for conventional protein meals (canola and cottonseed) at total inclusion levels of 0, 4, or 8% DM. Experiment 2 evaluated PSC as a partial replacement for an energy source (barley grain) at final inclusion levels of 0, 12, 15, or 30% DM. There was no interaction between level × processing type (P ≥ 0.10) in either experiment. In Experiment 1, neither the type nor the level of PSC affected methane production (mL/g digested DM). Replacement of canola or cottonseed meal with PSC reduced (P < 0.01) in vitro dry matter digestibility (IVDMD) by an average of 7% across all PSC types and inclusion levels compared with the control. However, total volatile fatty acid (VFA) concentrations were not affected by PSC type or level. In Experiment 2, inclusion of PSC in a barley-based diet increased (P < 0.01) methane production (mL/g digested DM) by up to 20.8% compared with the control. IVDMD was not affected by PSC inclusion up to 15% DM (P > 0.05). Processing type had varying effects: PSC4 (hexane-extracted) had 5.5% greater IVDMD (P = 0.02) than PSC1 and 3.8% greater than PSC2 but was similar to PSC3—all three produced using the novel extraction methods. These findings suggest that PSC processed with novel extraction methods has potential as a feed ingredient, but its application requires careful consideration. While it can replace conventional protein meals without reducing total VFA production, this may occur at the cost of reduced diet digestibility. Furthermore, when PSC replaces barley grain, methane production may increase. The suitability of PSC therefore depends on the extraction method, inclusion level, and the dietary component it replaces.